Shareholder Activists and Frictions in the CEO Labor Market - Thomas Keusch (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
Using hand-collected data on CEO appointments during shareholder activism campaigns, this study examines whether shareholder involvement in CEO recruiting affects frictions in CEO hiring decisions. The results indicate that appointments of CEOs who are recruited with shareholder activist influence are followed by more favorable stock market reactions and stronger profitability improvements than CEO appointments that also occur during activism campaigns but without the influence of activists. I find little evidence that shareholder activists increase hiring frictions by facilitating the recruiting of CEOs who will implement myopic corporate policies. Analyses of recruiting process characteristics reveal that activist influence is associated with more resources being dedicated to the CEO search process and with a higher propensity to recruit CEOs from outside the firm. These findings contribute to the CEO labor market literature, which tends to focus on the decision to remove incumbent CEOs but provides limited insights into CEO recruiting.
urn:nbn:de:hebis:30:3-616598
Keywords: G23; G32; G34; M12; M51; 330; Executive labor market; corporate governance; shareholder activism